The Role of Dynamic Managerial Capabilities of School Principals on School Performance through Networking Capabilities and Spiritual Motivation - Kholid, Kholid; Suyanto, Bagong; Nadia, Fiona Niska Dinda (RSF Conference Series: Business, Management and Social Sciences, 2023)
This study was conducted in the educational settings of the East Java Integrated Islamic School Network (JSIT), encompassing Kindergarten to High School levels. This study examines the impact of dynamic managerial ability, spiritual motivation, and networking ability on school performance across all East Java Integrated Islamic School Network levels. To achieve the research objective, a mixed-methods approach involving quantitative and qualitative interviews was employed. Empirical evidence revealed that the Principal’s Dynamic Managerial Ability significantly influences School Performance. Furthermore, Spiritual Motivation has a notable impact both on the Principal’s Dynamic Managerial Ability and directly on School Performance. In contrast, while Networking Ability does not significantly affect the Principal’s Dynamic Managerial Ability, it does have a marked influence on School Performance. Additionally, Spiritual Motivation and Networking Ability significantly affect School Performance mediated by the Principal’s Dynamic Managerial Ability.